Damage to the human quadriceps muscle from eccentric exercise and the training effect - Bowers, E. J.; Morgan D. L.; Proske, U. (Journal of Sports Sciences, 2004)
Nine participants performed two bouts of a step exercise, during which the quadriceps muscle of one leg acted eccentrically. Before and after the exercise, isokinetic torque was measured over a range of knee angles to determine the optimum angle for torque. Immediately after the first bout of exercise, the quadriceps showed a significant (P?<?0.05) shift of 15.6±1.4° (mean±s&xmacr;) of its optimum angle in the direction of longer lengths, suggesting the presence of damage. A drop in peak torque, together with delayed soreness and swelling, confirmed that damage to muscle fibres had occurred. After the second bout of exercise, 8 days later, the shift in optimum angle was 10.4±1.0°, which was significantly less than after the first bout (P?<?0.05). Other indicators of damage were also reduced. In addition, the muscle exhibited a sustained shift in optimum angle (3.4±0.9°), suggesting that some adaptation had taken place after the first bout of exercise. We conclude that muscles like the quadriceps can show evidence of damage after a specific programme of eccentric exercise, followed by an adaptation response. This is despite the fact that the quadriceps routinely undergoes eccentric contractions in everyday activities.